Mung bean juice as a phytotherapy development to increase hemoglobin levels in adolescent girls, Banten, Indonesia - Khotimah, Husnul; Rahayu, Trio Gustin; Rochman, Dadang (Fakultas Ilmu Kesehatan, 2024)
Adolescent girls are very susceptible to anemia due to growth and the arrival of menstruation. Providing food that is expected to increase iron adequacy in adolescents is mung bean juice, because mung beans can prevent a decrease in hemoglobin levels. The aim of this research is to determine the effect of drinking mung bean juice on increasing hemoglobin levels in adolescent girls. The research is pre-experimental analytical research with a One group pre-test post-test design approach. The population in this study were all 12 young women at Al Hadi High School. The sample in this study was all 12 young women at Al Hadi High School Banten. The sampling technique is total sampling. The data analysis used in this research was the paired T test. The results of the study showed that there was a strong relationship between giving mung bean juice and increasing hemoglobin levels in young women (p=0.002). Adolescents are expected to have awareness and understanding of nutritional requirements as an effort to prevent anemia in adolescents and encourage young women to regularly consume mung bean juice.